Socio-Economic Conditions of Fishermen's Community in South Nagari Tiku, Agam Regency - Murhenna Uzra; Irwan Febrianto; Siti Aisyah (Berkala Perikanan Terubuk, 2023)
This research examines the socio-economic conditions of fishermen in Nagari Tiku Selatan due to the influence of life phenomena and natural disasters that recently hit almost all over the world. The consequences of this phenomenon have a negative impact on people's lives and economic conditions on household income. Various prevention efforts are carried out by both the central and regional governments. For Nagari Tiku Selatan, community leaders and traditional leaders are active in overcoming this condition. One of the efforts made is the local wisdom ritual of rejecting reinforcements which is believed to be able to help restore the economic situation of the people in Nagari Tiku Selatan. The method in this study was collecting primary and secondary data, conducting active interviews with the help of a questionnaire that had been inserted. The results show that the tradition of rejecting reinforcements is carried out if there are signs of a decrease in production or yields and the income of fishermen and farmers in Nagari Tiku Selatan. The ceremony of turning back reinforcements was carried out as a form of economic recovery for fishermen and farmers after going through difficult times in terms of income which could not be separated from the elements of natural disasters and the community's negligence towards religious norms and customary regulations in the social environment of the community in Nagari Tiku Selatan. Rejecting Bala activities as a hereditary activity is believed to be able to return the community's economic situation to a better direction after facing other calamities that hit the economy of the people of Nagari Tiku Selatan.